Combination Chemo‐Immunotherapy for Pancreatic Cancer Using the Immunogenic Effects of an Irinotecan Silicasome Nanocarrier Plus Anti‐PD‐1. Issue 6 (27th January 2021) - Liu, Xiangsheng; Jiang, Jinhong; Liao, Yu‐Pei; Tang, Ivanna; Zheng, Emily; Qiu, Waveley; Lin, Matthew; Wang, Xiang; Ji, Ying; Mei, Kuo‐Ching; Liu, Qi; Chang, Chong Hyun; et al.
Abstract: There is an urgent need to develop new life‐prolonging therapy for pancreatic ductal adenocarcinoma (PDAC). It is demonstrated that improved irinotecan delivery by a lipid bilayer coated mesoporous silica nanoparticle, also known as a silicasome, can improve PDAC survival through a chemo‐immunotherapy response in an orthotopic Kras‐dependent pancreatic cancer model. This discovery is premised on the weak‐basic properties of irinotecan, which neutralizes the acidic lysosomal pH in PDAC cells. This effect triggers a linked downstream cascade of events that include autophagy inhibition, endoplasmic reticulum stress, immunogenic cell death (ICD), and programmed death‐ligand 1 (PD‐L1) expression. ICD is characterized by calreticulin expression and high‐mobility group box 1 (HMGB1) release in dying Kras‐induced pancreatic cancer (KPC) cells, which is demonstrated in a vaccination experiment to prevent KPC tumor growth on the contralateral site. The improved delivery of irinotecan by the silicasome is accompanied by robust antitumor immunity, which can be synergistically enhanced by anti‐PD‐1 in the orthotopic model. Immunophenotyping confirms the expression of calreticulin, HMGB1, PD‐L1, and an autophagy marker, in addition to perforin and granzyme B deposition. The chemo‐immunotherapy response elicited by the silicasome is more robust than free or a liposomal drug, Onivyde. The silicasome plus anti‐PD‐1 leads to significantly enhanced survival improvement, and is far superior to anti‐PD‐1 plus either free irinotecan or Onivyde. Abstract : Improved irinotecan delivery by silicasome can improve pancreatic ductal adenocarcinoma (PDAC) survival through a chemo‐immunotherapy response when combined with anti‐PD‐1 in an orthotopic Kras‐dependent PDAC model. This discovery is premised on the weak‐basic properties of irinotecan, which neutralizes the acidic lysosomal pH and triggers a linked downstream cascade of events that include autophagy inhibition, endoplasmic reticulum stress, immunogenic cell death, and PD‐L1 expression.